Kewajiban dan Tanggung Jawab Memenuhi Prestasi dalam Hukum Jaminan - Inri Januar (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Abstract Law has an important role in the world economy , because the presence of lenders have made the position of the legal protection of the guarantee provided by the debtor. It should be alert to who is obliged to meet the achievement, and who is responsible for fulfilling achievement, it is to see if the position of individual guarantees directly replace the debtor at the time of default. Assurance also give priority to who is to first get the fulfillment of receivables if the debtor has turned out to be propagators of the creditor and the debtor turns out possessions is not enough to meet all its debts. Kata Kunci: tanggung jawab memenuhi prestasi